Pendekatan Konseling Kelompok Analisis Transaksional Untuk Meningkatkan Motivasi Belajar Peserta Didik SMP - Siti Nurdiyaningsih; Asrowi Asrowi; Rian Rokhmad Hidayat (Jurnal Psikoedukasi dan Konseling, 2022)
Abstract: The aim of this research was to know the effectiveness of Transactional Analysis group counselling guiding book to improve students’ motivation. This was a Research and Development (R&D). The subjects  of  this  research  was  consist  of  subject  expert  test,  practitioners subject, and the subject of a small group. Data collection technique used questionnaire. Data analysis used Interrater Agreement Model and Wilcoxon Sign Rank Test. The result of analysis showed that test index of Interrater Agreement Model has very good validity with accountability almost  perfect  agreement,  it  meant  the two  experts  gave same assessment to the AT counselling group guiding book. The result from that test is supported by Wilcoxon Sign Rank Test, that was showed there was difference between pre-test score and post-test score of experimental group after given treatment  in  the  form  of  Transactional  Analysis  Group counselling.   The conclusion  of  this  research  was  Transactional  Analysis Group  counselling approach was effective to improve students’ motivation. Abstrak: Tujuan penelitian ini adalah untuk mengetahui tingkat efektifitas buku pedoman konseling  kelompok AT untuk meningkatkan motivasi belajar Siswa SMP. Penelitian ini merupakan penelitian pengembangan. Subjek dalam penelitian ini meliputi subjek uji ahli, subjek praktisi, dan subjek kelompok kecil. Teknik pengumpulan data menggunakan angket dengan menggunakan Interrater Agreement Model dan Wilcoxon Sign Rank Test. Hasil analisis menunjukkan bahwa indeks hasil uji ahli dari Uji Interrater Agreement Model penilaian buku panduan oleh kedua  ahli  memiliki  validitas  sangat  baik  dengan  tingkat kehandalan  almost perfect agreement. Hasil dari uji tersebut didukung dengan Uji Wilcoxon Sign Rank Test, yang menunjukkan bahwa terdapat perbedaan antara nilai pretest dengan nilai postest kelompok eksperimen setelah diberikan treatment  berupa konseling kelompok Analisis Transaksional. Simpulan penelitian ini adalah pendekatan konseling kelompok Analisis Transaksional efektif untuk meningkatkan  motivasi  belajar  siswa.